Are there specific translational challenges in regenerative medicine? Lessons from other fields. (October 2015) - Gardner, John; Faulkner, Alex; Mahalatchimy, Aurélie; Webster, Andrew
There is concern that translation 'from bench to bedside' within regenerative medicine (RM) will fail to materialize, or will be dismally slow, due to various challenges arising from the highly novel and disruptive nature of RM. In this article, we provide a summary of these challenges, and we critically engage with the notion that such challenges are specific to RM. It is important, we argue, not to overstate the exceptional nature of RM, as valuable lessons can be learned from elsewhere in medicine. Using several examples of technology adoption, we suggest that emerging RM products and procedures will have to work hard to find or create an adoption space if translation into the clinic is to be successful.